Effects of Gypsum on Trace Metals in Soils and Earthworms. Issue 1 (1st January 2014) - Chen, Liming; Kost, Dave; Tian, Yongqiang; Guo, Xiaolu; Watts, Dexter; Norton, Darrell; Wolkowski, Richard P.; Dick, Warren A.
Abstract : Mined gypsum has been beneficially used for many years as an agricultural amendment. A large amount of flue gas desulfurization (FGD) gypsum is produced by removal of SO2 from flue gas streams when fuels with high S content are burned. The FGD gypsum, similar to mined gypsum, can enhance crop production. However, information is lacking concerning the potential environmental impacts of trace metals, especially Hg, in the FGD gypsum. Flue gas desulfurization and mined gypsums were evaluated to determine their ability to affect concentrations of Hg and other trace elements in soils and earthworms. The study was conducted at four field sites across the United States (Ohio, Indiana, Alabama, and Wisconsin). The application rates of gypsums ranged from 2.2 Mg ha −1 in Indiana to 20 Mg ha −1 in Ohio and Alabama. These rates are 2 to 10 times higher than typically recommended. The lengths of time from gypsum application to soil and earthworm sampling were 5 and 18 mo in Ohio, 6 mo in Indiana, 11 mo in Alabama, and 4 mo in Wisconsin. Earthworm numbers and biomass were decreased by FGD and mined gypsums in Ohio. Among all the elements examined, Hg was slightly increased in soils and earthworms in the FGD gypsum treatments compared with the control and the mined gypsum treatments. The differences were not statistically significant except for the Hg concentration in the soil at the Wisconsin site. Selenium in earthworms in the FGD gypsum treatments was statistically higher than in the controls but not higher than in the mined gypsum treatments at the Indiana and Wisconsin sites. Bioaccumulation factors for nondepurated earthworms were statistically similar or lower for the FGD gypsum treatments compared with the controls for all elements. Use of FGD gypsum at normal recommended agricultural rates seems not to have a significant impact on concentrations of trace metals in earthworms and soils.